Computer use by People with Aphasia: A Survey Investigation. Issue 2 (18th September 2014) - Finch, Emma; Hill, Anne J.
<x content-type="archive" xml:space="preserve">Abstract</x> Computers are encountered increasingly in the clinical setting, including during aphasia rehabilitation. However, currently we do not know what people with aphasia think about using computers in therapy and daily life, or to what extent people with aphasia use computers in their everyday life. The present study explored: (1) the use of computers by people with aphasia; and (2) the perceptions of people with aphasia towards computers and computer-based therapy. Thirty-four people with aphasia completed an aphasia-friendly paper-based survey about their use of computers before and after the onset of their aphasia, and their attitudes towards computer-based aphasia therapy. There was a high level of computer usage by people with aphasia both before and after the onset of their aphasia. However, the nature of the computer use changed following aphasia onset, with a move away from work-based usage. The majority of the cohort used computers for aphasia therapy and liked using computer-based aphasia therapy, provided that the programs were perceived as appropriate for their individual needs. The results highlight the importance of exposing people with aphasia to computer-based aphasia therapy in a supported clinical environment, and the need to ensure that computer-based therapy is individualised for each client. It should be noted, however, that while the majority of participants reported positive experiences with using computers, this does not mean that the computer-based therapy software used was necessarily an effective treatment for aphasia.